PENGARUH PELATIHAN BAYANGAN (SHADOW) BULUTANGKIS TERHADAP PENINGKATAN KELINCAHAN DAN KECEPATAN REAKSI - Arya Kusuma, Gusti Ngurah (Universitas Pendidikan Ganesha, 2013)
The purpose of this research was to find out the effect of badminton shadow training toward the increased agility and speed of reaction. The type of research was a quasi-experimental and the design of research was the non-randomized pretest-posttest control group design. The subjects were man’s student badminton extracurricular participants of SMAN 4 Singaraja. Agility and speed of reaction posttest to the treatment group and the control group were analyzed by independent t-test at significance 0,05 with SPSS 16.0. Based on independent t-test results were showed : (1) to the agility variable, the comparison of the treatment and the control group values ​​obtained t = 2,724, with a significance value of 0,011, (2) to the speed of reaction variable, the comparison of the treatment and the control group values ​​obtained t = 2,524, with a significance value of 0,018. Calculated significance value smaller than the value of 0,05 (Sig < 0.05), thus the research hypothesis